Damage Characterization of Polypropylene Honeycomb Sandwich Panels Subjected to Low-Velocity Impact - Freeda A. Amir; A. R. Othman; H. Md. Akil (Advances in Materials Science and Engineering, 2013)
The post-test deformation and failures of sandwich composites may involve complex interactions between various failure mechanisms. In this study, the extent of impact damages and response of the thermoplastic honeycomb sandwich are analysed through energy profile diagrams and associated load history curves. The degree of the postimpact damages of the sandwich is further characterized using an optical surfaces metrology analysis. The thickness of the honeycomb was found to influence the extent of the damage which occurred following the low-velocity impact. Thicker core was able to sustain a higher load as well as the energy absorption before total failure occurred.